Calcareous‐support nanoscale Zero‐valent iron: New findings on adsorption of Cr(VI) in aqueous solution - Armand N. Tchakounte (Journal of Applied Surfaces and Interfaces, 2019)
This work focuses on Cr(VI) sorption by Calcareous and nZVI/Calcareous was investigated. The purpose of this study is to understand the mechanisms that govern the elimination of Cr (VI) and to find a suitable kinetics model of removal. Spectroscopic studies including FTIR, (TG‐DSC), SEM, Methylene blue and Iodine number were used for its characterization. Equilibrium data was examined using a comparison of linear Langmuir, Freundlich, Temkin and Dubinin– Radushkevich isotherm models. The Freundlich isotherm provided the best fit to the experimental data for Cr(VI) ions as indicated by the values of the regression coefficient. The kinetic rates were modeled by using the Lagergren‐first‐order, pseudo‐second‐order, Elovich and Intraparticle diffusion model. The Elovich model was found to explain the adsorption kinetics most effectively. The presence of intra‐particle diffusion mechanism was prominent, although it was not the sole rate‐determining step. The results showed that Calcareous and nZVI/Calcareous, can be effective for removing Cr(VI) ions from solution.